Autopolymerized poly(methyl methacrylate) reinforced with alumina nanoparticles - Baloš Sebastian; Petronijević-Šarčev Branislava; Šarčev Ivan; Mirković Siniša; Pilić Branka; Baloš Tatjana; Janjatović Petar (Vojnosanitetski Pregled)
Background/Aim. Mechanical properties, most significantly flexural strength of cold polymerized acrylic dental materials, used for denture reparation are lower compared to the equivalent hot polymerized materials. This paradox can be rectified by the application of alumina nanoparticles, which was the aim of this work. Methods. The liquid component of the commercial autopolymerized denture reline resin was modified with 0.05%, 0.2% and 1.5% (wt) 13 nm hydrophobic Al2O3. These mixtures, along with the unmodified liquid, were mixed with the powder component to form test specimens. Flexural modulus and strength were tested, while the results were statistically evaluated by the oneway ANOVA analysis followed by Tukey’s test. Differential scanning calorimetry, scanning electron microscopy and energy dispersive X-ray analysis were performed to assess the heat and fracture surface features. Results. A statistically significant increase in flexural modulus was obtained only for 0.2% nanoparticle content, while flexural strength was significantly increased for specimens modified with 0.05% and 0.2% nanoparticles. Moreover, the rise of nanoparticle content to 1.5% contributed the formation of agglomerates, giving unsatisfactory mechanical properties. Also, the rise in glass transition temperature was noted for the most effective 0.05 and 0.2% Al2O3 contents. Conclusion. The 0.2% 13 nm Al2O3 loading is the most effective in improving the tested mechanical properties of cold polimerized poly(methyl methacrylate) reline resin.